Cách này hơi dài chút, nhưng nếu nghĩ ra cách hay hơn mình sẽ đề xuất nhe!
\(=\int\sin^5x.\left(2\sin x\cos x\right)^3.2xdx=16\int x.\sin^8x\cos^3xdx\)
\(\left\{{}\begin{matrix}u=x\\dv=\sin^8x.\cos^3xdx\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}du=dx\\v=\int\sin^8x.\cos^3xdx\end{matrix}\right.\)
\(I_1=\int\sin^8x\cos^3xdx=\int\sin^8x.\cos^2x.\cos xdx=\int\sin^8x.\left(1-\sin^2x\right)\cos xdx\)
\(t=\sin x\Rightarrow dt=\cos xdx\Rightarrow\int\sin^8x\left(1-\sin^2x\right)\cos xdx=\int(t^8-t^{10})dt=\dfrac{1}{9}t^9-\dfrac{1}{11}t^{11}=\dfrac{1}{9}\sin^9x-\dfrac{1}{11}\sin^{11}x\)
\(\Rightarrow\left\{{}\begin{matrix}du=dx\\v=\dfrac{1}{9}\sin^9x-\dfrac{1}{11}\sin^{11}x\end{matrix}\right.\)
\(\Rightarrow\dfrac{I}{16}=x.\left(\dfrac{1}{9}\sin^9x-11\sin^{11}x\right)-\int\left(\dfrac{1}{9}\sin^9x-\dfrac{1}{11}\sin^{11}x\right)dx\)
\(I_2=\int\left(\dfrac{1}{9}\sin^9x-\dfrac{1}{11}\sin^{11}x\right)dx=\dfrac{1}{9}\int\sin^9xdx-\dfrac{1}{11}\int\sin^{11}xdx\)
À thế này là xong rồi còn gì :) Bạn tự làm nốt nhé